Can electricity liberalisation foster the development of radical clean-energy technologies? - Matteo Romagnoli (Fondazione Eni Enrico Mattei (FEEM), 2022)
The paper investigates the effect of electricity liberalisation on the variety of clean energy patent' search space to asses whether a more competitive electricity market can foster the development of radical clean-energy technologies. This idea is tested using a cross-section of patents filed in the period 1990-2017, a set of patent-level indicators and an instrumental variable approach. Results show that electricity liberalisation pushes clean-energy patents to cite knowledge from technological fields other than their own. However, the reform does not significantly affect the overall breath of the knowledge base of these patents. Additional insights are drawn by looking at the correlation between electricity liberalisation and an indicator of novelty in patents' search space. The results are consistent with the claim that electricity liberalisation has a positive effect on the development of radical clean-energy technologies. At the same time, by describing how the reform changes clean-energy patents' search space, they define this effect more precisely.
Keywords: L94; O31; Q42; Q55; 330; Clean-energy Technologies; Electricity Liberalisation; Climate Change; Patent Data